New reductive addition of hard nucleophiles to 6,7-bis(methylsulfanyl)-1,4-dihydro-1,4-methanonaphthalene-5,8-dione - Di Vitta, C.; Campos, IPD; Farah, JPS; Zukerman-Schpector, J. (Royal Soc Chemistry, 2000)
A new reaction mode of 6,7-bis(methylsulfanyl)-1,4-dihydro-1,4-methanonaphthalene-5,8-dione 1 with the hard nucleophiles sodium benzene- or methane-sulfinate and cyanide, in DMSO, at room temperature, leads to the unexpected hydroquinonoid products 3a-c. All the data are in agreement with a mechanistic pathway involving the initial attack of the hard nucleophile onto the hard carbonyl group, followed by a symbiotic re-attack of the oxygen on the incoming group. In the case of soft nucleophiles, reaction on the olefinic carbon of the enedione system is preferential.